Dynamics of the Koshi River on the Perspective of Morphology and Sedimentation with Emphasis on Post Disaster Impact of the 2008 Koshi Flood - Kafle, K.R.; Khanal, S.N.; Dahal, R.K. (Kathmandu University Journal of Science Engineering and Technology, 2015)
The Koshi river is one of the most dynamic rivers in the world. It has shifted about 115 km westward due to sedimentation and tectonic activities during the past 200 years. Dynamic nature of the Koshi is revealed by its erosive nature and high capacity of carrying silt and sand from highlands. Disaster from floods are frequent in this river channel because of encroachment in watershed, high denudation rate, torrential rainfall in the upland as well as poor design of manmade structures along the river channel.